2023
DOI: 10.2174/0929867329666220801165849
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antioxidant Properties of Organoselenium Compounds

Abstract: Background: The chemistry of organoselenium reagents provides an asset for organic synthesis. The versatility of these reagents as electrophiles and nucleophiles makes them one of the key components of organic synthesis. Various synthetic transformations such as oxyselenenylations, selenocyclization and selenoxide elimination have been successfully achieved using organoselenium reagents under mild reaction conditions. The presence of selenocysteine in a few mammalian enzymes was the key information for seleniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 136 publications
0
10
0
Order By: Relevance
“…Se nanoparticles with chitosan/citrate complex have protected experimental mice against ROS in galactose-induced aging [ 134 ]. Mamgain et al reported the antioxidant activity of diverse Se-based nanoparticles [ 135 ]. The antioxidant, anti-carcinogenic, and immunomodulatory efficacy of nano-Se applications for enhancing stress resilience and productivity of livestock and fish were proven by Sarkar et al [ 136 ].…”
Section: Nanoformulations Of Se In Age-related Disordersmentioning
confidence: 99%
“…Se nanoparticles with chitosan/citrate complex have protected experimental mice against ROS in galactose-induced aging [ 134 ]. Mamgain et al reported the antioxidant activity of diverse Se-based nanoparticles [ 135 ]. The antioxidant, anti-carcinogenic, and immunomodulatory efficacy of nano-Se applications for enhancing stress resilience and productivity of livestock and fish were proven by Sarkar et al [ 136 ].…”
Section: Nanoformulations Of Se In Age-related Disordersmentioning
confidence: 99%
“…Organoselenium derivatives are found in many important bioactive compounds, 1 exhibiting a wide array of beneficial properties, including anti-oxidant, 2 anti-inflammatory, 3 anti-hypertensives, 4 and anti-infective effects. 5 Furthermore, they are highly versatile reagents in organic synthesis and catalysis, 1 a ,6 providing significant motivation for chemists to explore innovative methods for their synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Excess of ROS was ameliorated by some natural enzymatic preventive antioxidants such as catalases, superoxide dismutase, and the GPx-enzymes in biological systems . A variety of organoselenium compounds as antioxidants have been developed to mimic the action of the GPx-enzymes. , In this regard, the first synthetic heterocyclic organoselenium compound as ebselen (2-phenyl-1,2-benzoisoselenazol-3-[2 H ] one, 1 ) with the Se–N bond in a five-membered ring was discovered as the GPx-mimic (Figure ). …”
Section: Introductionmentioning
confidence: 99%